Application of Topology in Variety Fields - Sodikkhujaeva Shakhnoza (Genius Journals, 2022)
Topology although one of the recently invented sciences in mathematics, it is widely used in many areas of human life. In this paper we discuss some applications in various fields of Science and Technology, like applications to Biology, Robotics, GIS, Error-coding and Genetics. Being a part of theoretical mathematics, the laws of topology are finding more and more application in various types of human activities that are described by rules and laws of topology
Keywords: topology; genotypes; genotype-phenotype relationship; sequences